Genomic sequences of five novel HLA class I alleles: A*30:129, B*08:195, B*51:01:62, C*01:147 and C*12:195:02. (24th May 2018) - Balas, A.; Alenda, R.; Moreno‐Hidalgo, M. A.; García‐Sánchez, F.; Vicario, J. L.
Abstract : Five new HLA class I alleles are described, A*30:129, B*08:195, B*51:01:62, C*01:147 and C*12:195:02 .